The effect of board of directors characteristics on risk and bank performance: Evidence from Turkey - Doğan, Berna; Ekşi, İbrahim Halil (Economics and Business Review, 2020)
A bank, particularly in developing countries like Turkey, is one of the most important institutions in the financial sector. Therefore knowing the factors affecting the performance of banks is important for the development of the sector. One of the factors affecting the risk and profitability of banking sector is the internal factors of the banks. The aim of this paper is to investigate the board of directors’ characteristics and its effect on risk level measured by non-performing loans and on bank performance measured by asset profitability using the Generalized Method of Moments (GMM) estimator. Data from nineteen deposit banks for the period 2012–2018 were used. The result of the study determined that the board size, foreign board members and the independent board members have an effect on both non-performing loans and the return on assets.